Exploring Religious Terms in Islam: Opportunity and Challenge of Teaching and Learning Islam - Mujazin Mujazin (Pusat Riset dan Inovasi Nasional, 2024)
The concept of religious terms are significant for the sake of teaching and learning Islam and pertains to expressions derived predominantly from one or more religious books. This study seeks to delve into the religious terms and expressions present in the book